Relationship between HIV integrase polymorphisms and integrase inhibitor susceptibility: An in silico analysis - Hotma Martogi Lorensi Hutapea; Yustinus Maladan; Widodo (Heliyon, 2018)
Integrase (IN) plays an essential role in HIV-1 replication, by mediating integration of the viral genome into the host cell genome. IN is a potential target of antiretroviral (ARV) therapeutic drugs such as ALLINI, Raltegravir (RAL), and Elvitegravir (EVG). The effect of IN polymorphisms on its structure and binding affinity to the integrase inhibitors (INIs) is not well understood. The goal of this study was to examine the effect of IN polymorphisms on its tertiary structure and binding affinities to INIs using computational approaches. HIV genomes were isolated from patient blood and the IN gene was sequenced to identify polymorphisms. Protein structures were derived using FoldX and the binding affinity of IN for ALLINI, RAL, and EVG was evaluated using a molecular docking method. The binding affinities of ALLINI and EVG for wild-type IN were lower as compared to an IN variant; in contrast, the binding affinity of RAL for the IN variant was lower as compared to wild-type IN. These results suggested that IN variant interacts with ALLINI and EVG more efficiently as compared to the wildtype, which may not cause resistent to the drugs. In vitro and in vivo studies should be done to validate the findings of this study.